A puzzle‐based material handling system for order picking. (12th October 2020) - Shekari Ashgzari, Mina; Gue, Kevin R.
Abstract: We propose a new type of automated goods‐to‐person system based on a grid of unit‐sized conveyors. The system uses a negotiation‐based decentralized control algorithm to route required totes or cartons to one or more picking positions on the perimeter of the grid. We describe the algorithms to accomplish a "puzzle‐like" movement of totes on the grid and explore several design parameters and their effects on system throughput. One interesting result is that a 77% increase in throughput is possible if the orders processed by different workstations have no SKU commonality. The degree of stock keeping unit (SKU) commonality also affects the choice of layout.